PENGARUH KOMPETENSI PEDAGOGIK GURU DAN FASILITAS BELAJAR DI RUMAH TERHADAP MOTIVASI BELAJAR SISWA KELAS X IIS DI SMA NEGERI 5 PEKANBARU - Br. Hutabarat, Renita; Sumarno, Sumarno; Hendripides, Hendripides (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to determine the effect of teacher pedagogical competencies and learning facilities at home on the learning motivation of IIS class X students in Pekanbaru 5 Senior High School. The population in this study were all students of class X IIS SMA 5 pekanbaru which amounted to 143 students. The samples was taken using a simple random sampling technique that is as many as 57 students. Data was collected using questionnaires, data analysis using descriptive analysis and multiple linear regression. Descriptively, students' learning motivation is included in the low category, the teacher's pedagogical competence is included in the good category, and home learning facilities are in the inadequate category. Teacher's pedagogic competence and home learning facilities have a significant effect on learning motivation with the regression equation Y = 0.209 + 0.438X1 + 0.305X2 and contribute influence to student learning motivation by 53.4%.Key Words: Teacher Pedagogic Competency, Learning Facilities In Home, and Learning Motivation.